A novel constrained H2 optimization algorithm for mechatronics design in flexure-linked biaxial gantry. (November 2017) - Ma, Jun; Chen, Si-Lu; Kamaldin, Nazir; Teo, Chek Sing; Tay, Arthur; Mamun, Abdullah Al; Tan, Kok Kiong
Abstract: The biaxial gantry is widely used in many industrial processes that require high precision Cartesian motion. The conventional rigid-link version suffers from breaking down of joints if any de-synchronization between the two carriages occurs. To prevent above potential risk, a flexure-linked biaxial gantry is designed to allow a small rotation angle of the cross-arm. Nevertheless, the chattering of control signals and inappropriate design of the flexure joint will possibly induce resonant modes of the end-effector. Thus, in this work, the design requirements in terms of tracking accuracy, biaxial synchronization, and resonant mode suppression are achieved by integrated optimization of the stiffness of flexures and PID controller parameters for a class of point-to-point reference trajectories with same dynamics but different steps. From here, an H 2 optimization problem with defined constraints is formulated, and an efficient iterative solver is proposed by hybridizing direct computation of constrained projection gradient and line search of optimal step. Comparative experimental results obtained on the testbed are presented to verify the effectiveness of the proposed method. Abstract : Highlights: To formulate the mechatronics design problem in gantry stage as a constrained H2 optimization problem. The constraints come from decentralized nature of the control architecture, and the force exertion on multi-bodies. Since there is no standard formulae for this constrained H2 problem, we convert it to a projection gradient-based optimization problem on a constrained hyperplane. The optimization problem is then solved by hybridizing direct computation and line search iteratively, and fast convergence of functional cost is achieved. The real-time experiment on the actual testbed shows practical appeal of proposed design approach.